2019
DOI: 10.1002/jcp.28730
|View full text |Cite
|
Sign up to set email alerts
|

circLRP6 regulates high glucose‐induced proliferation, oxidative stress, ECM accumulation, and inflammation in mesangial cells

Abstract: Aberrant regulation in mesangial cell proliferation, extracellular matrix (ECM) accumulation, oxidative stress, and inflammation under hyperglycemic condition contributes significantly to the occurrence and development of diabetic nephropathy (DN). However, the mechanisms underlying the hyperglycemia-induced dysregulations have not been clearly elucidated. Here, we reported that high mobility group box 1 (HMGB1) was highly elevated in high glucose (HG)-treated mesangial cells, and induced the phosphorylation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
78
0
18

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 35 publications
3
78
0
18
Order By: Relevance
“…But, a handful of researches uncovered that circRNAs participated in regulating inflammatory response and affected the progression of inflammation‐associated ailments. One research attested that circLRP6 mediated high glucose (HG)‐engendered mesangial cells oxidative stress and inflammation . Moreover, Zhao et al discovered that hsa_circ_0018429, hsa_circ_0026579, hsa_circ_0099188, and hsa_circ_0012535 were both increased in the blood from community‐acquired pneumonia (CAP) patients, which might be the crucial diagnostic biomarkers for CAP .…”
Section: Introductionmentioning
confidence: 99%
“…But, a handful of researches uncovered that circRNAs participated in regulating inflammatory response and affected the progression of inflammation‐associated ailments. One research attested that circLRP6 mediated high glucose (HG)‐engendered mesangial cells oxidative stress and inflammation . Moreover, Zhao et al discovered that hsa_circ_0018429, hsa_circ_0026579, hsa_circ_0099188, and hsa_circ_0012535 were both increased in the blood from community‐acquired pneumonia (CAP) patients, which might be the crucial diagnostic biomarkers for CAP .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, circRNA LRP6 contributes to high-glucose-induced inflammation and extracellular matrix accumulation in mesangial cells by sponging miR-205. 10) circPTN regulates proliferation activity in glioma by targeting miR-145-5p/miR-330-5p. 30) Accumulating evidence points to the potential role of miRNAs in DKD progression.…”
Section: Discussionmentioning
confidence: 99%
“…4,7,8) Our previous study indicated that pyroptosis is involved in tubular injury in diabetes, as evidenced by GSDMD p30 fragment generation and flow cytometry analysis. 9) Understanding the molecular cascades regulating pyroptosis will yield additional targets for DKD treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…diabetic nephropathy (dn) is becoming the most pervasive complication for both types i and ii diabetes, and is also the major cause of end-stage renal disease in the majority of developed and developing countries (1). clinically, dn is characterized by mesangial hypertrophy, mesangial cell (Mc) proliferation, albuminuria, extracellular matrix (ecM) accumulation and kidney fibrosis (2,3).…”
Section: Introductionmentioning
confidence: 99%